Kenosis and nature - Rolston, Holmes, 1932-2025, author; Wm. B. Eerdmans Publishing Co., publisher (Colorado State University. Libraries, 2001)
"Kenosis" is the theological idea of self-emptying, usually applied to divine self-emptying in the life of Jesus. Is there kenosis in nature? This might seem unlikely with selfish genes and survival of the fittest, self-defense and self-actualizing. But beyond self-identity, there is defense of species identity, inclusive and shared fitness, interdependence and symbiosis. In sexuality and reproduction, and regeneration, organisms care for others, give themselves over to the next and future generations. In cruciform nature, there is suffering that life may continue, with individuals sacrificed for ongoing life. A non-deliberated kenosis is part of the biological order, but deliberated kenosis only comes with human life.
Keywords: sexuality; kenosis; self-emptying; regeneration; selfish genes; cruciform nature; self-defense; self-actualizing; self-sacrifice; shared fitness; reproduction; species identity